PEMBUATAN BIOPESTISIDA BERBASIS HIDROSOL TUMBUHAN SAPU-SAPU (Baeckea Frutescens L.) - Nyayu Siti Khodijah; Occa Roanisca; Ismed Inonu (Universitas Mataram, 2026)
The use of synthetic chemical pesticides in modern agriculture has negative impacts on the environment and health, necessitating more environmentally friendly pest control alternatives. One local potential that can be utilized is the broom plant (Baeckea frutescens L.), which is rich in secondary metabolites and essential oils with insecticidal activity. This community service program was implemented in Mapur Village, Bangka Regency, with the aim of empowering the community through the transfer of technology for producing broom hydrosol-based biopesticides. Implementation methods included outreach, formulation training, production assistance, packaging design, and digital marketing strategies. The results of the activity showed an increase in community capacity in processing broom leaf distillation waste into ready-to-use biopesticides. Field application tests showed a 40–60% reduction in pest attacks after two weeks of regular use. This program not only improved the community's technical skills but also fostered environmental awareness and strengthened village independence in utilizing local resources, as well as making this broom hydrosol biopesticide a superior village product.